Visualising urban gentrification and displacement in Greater London. - Zhang, Yuerong; Chapple, Karen; Cao, Mengqiu; Dennett, Adam; Smith, Duncan (Environment & Planning A, 2020)
Gentrification has long been a contentious issue which has prompted debate among scholars due to variations in its location, timing, context and types of measurements used. Therefore, it is worth seeking a simple and effective approach to measure the processes of gentrification, which enables comparative studies to be conducted across different cities around the world. Using six sets of thematic data from 2001 and 2011 at the neighbourhood level, this study proposes five types of gentrification and displacement by using Chapple and Zuk's theoretical framework. London was selected as a case study. The results show that gentrification was sweeping in many ways during the 2000s in London, particularly in Inner East London. Some areas in North West London are identified as vulnerable neighbourhoods at risk of displacement and gentrification. Furthermore, it was found that most of the neighbourhoods experiencing ongoing displacement are concentrated in Outer London and Inner South London. The typology provides a useful starting point for planners and policymakers to gain deeper insights into the progress of gentrification in London. Additionally, this work can serve as an example to illustrate the potential for using similar types of open source code and census data to estimate the degree of gentrification in other cities.